Further characterization of the DFNA1 audiovestibular phenotype - Lalwani, Anil K. (1998)
Background. Autosomal dominant, nonsyndromic, hereditary hearing impairment in a large Costa Rican kindred is caused by a mutation in the human homolog of the Drosophila diaphanous gene. Objective. To further characterize the phenotype of DFNA1 with comprehensive audiovestibular evaluation and computed tomography of the temporal bone. Patients One affected child and 2 affected adults of the Costa Rican kindred who harbor a mutation in the diaphanous gene. Setting. Medical Center at the University of California, San Francisco. Intervention Otologic and neuro-otologic examination; pure tone audiometry, speech audiometry, and immitance testing; auditory evoked potentials, electrocochleography, and otoacoustic emissions; electronystagmography and vestibular autorotation tests; and computed tomography of the temporal bone. Results The youngest subject, an 8-year-old boy, had a mild hearing loss, intact stapedial reflexes, otoacoustic emissions at high frequencies, normal auditory evoked potentials, and electrocochleographic findings consistent with endolymphatic hydrops. The two adults had severe to profound bilateral sensorineural hearing impairment. Electronystagmography disclosed normal vestibular function. Computed tomography demonstrated normal external, middle, and inner ear structures. Conclusions These results suggest that the early low-frequency hearing loss in this family is associated with endolymphatic hydrops. Elucidation of the role of the diaphanous gene in hearing will therefore lead to a better understanding of the mechanism of endolymphatic hydrops.